Variational study of polaron dynamics with the Davydov Ansätze - Luo, Bin (2011)
We derive explicit expressions for the amplitudes of the deviation vectors for the time-dependent Davydov D1, D2 and D ̃ Ansätze from the exact solution of the Schro ̈dinger equation for the Holstein polaron.